HUBUNGAN ANTARA JENIS KELAMIN, INTENSITAS BISING, DAN MASA PAPARAN DENGAN RISIKO TERJADINYA GANGGUAN PENDENGARAN AKIBAT BISING GAMELAN BALI PADA MAHASISWA FAKULTAS SENI PERTUNJUKAN - TANTANA, OLIVIA (E-Jurnal Medika Udayana; vol 3 no 3 (2014):e-jurnal medika udayana)
Balinese Gamelan noise intensity in one of it is instrument generates noise 90-115 dB. High noise intensity can affect hearing function. The purpose of this study was to determine the relationship between the gender, noise intensity, and length of exposure with the risk of noise induced hearing loss due to Balinese Gamelan on the faculty of performing arts students. Design of the study was cross sectional, the examination was done in 16-27 September 2013, morning before practice in campus of ISI Denpasar. All subjects was interviewed, underwent vital sign and routine ENT examination, tympanometry and pure tone audiometry. Incidence of hearing loss assessed from the presence of the acoustic notch on frequency 3000-6000Hz. The influence of gender, noise intensity, and length of exposure were analyzed with logistic regression. The subject of this study were 166 people. Incidence of noise induced hearing loss due Gamelan Bali 39.20%. In the multivariate analysis, factors that influenced the occurrence of hearing loss due to noise Balinese gamelan was length of exposure. The length of exposure more than 10 years with a value of p <0.01 and odd ratio=13.43 with 95% confidence interval (3.44 to 52.34). The length of exposure 6-10 years was significantly influenced with the value of p = 0.01 and odds ratio of 5.14 with 95% confidence interval (1.32 to 19.93). The length of exposure increased the risk of noise induced hearing loss due to Balinese Gamelan at the Performing Arts Faculty, sex and noise intensity did not affect significantly at the risk of noise induced hearing loss due to Balinese Gamelan at Faculty of Performing Arts. Given the magnitude of the incidence of noise-induced hearing loss Gamelan it is important to raise awareness of the dangers of noise induced hearing loss due to Balinese gamelan and avoid risk factors for hearing loss.
Keywords: hearing loss, noise, students of performing arts